Objective and Success-Stimulating Assessment of Students’ Knowledge Quality - Karayev Zhaumbay Amanturliyevich; Kobdikova Zhanartay Uazhytovna; Duisenova Raushan (Scientific Research and Experimental Development, 2024)
President K. Tokayev, at a meeting on the socio-economic development of the country held on April 19, 2023, highlighted certain problems in the field of education. Noting the low quality of knowledge among school students, he remarked that the country focuses not on quality but on high performance indicators. "There is a discrepancy between the grades students receive on the Unified National Testing (UNT) and their school grades; the difference between these grades can be 30% or more," said the head of state. Indeed, analysis shows that annually, on average, 25–30% of school graduates do not overcome the threshold level of the UNT, which corresponds to the lowest quality level—"recognition." Such a discrepancy indicates that schools have a "percentomania," stemming from an unobjective assessment of the quality of students’ knowledge. As is known, percentomania is the pursuit of high (percentage-wise) quantitative indicators at the expense of work quality. Considering this negative phenomenon, the president instructed the government to solve the problem of objectively assessing the knowledge acquired by students in school. Renowned educators [1,2,3,4], as well as we in our own research [5,6], have shown that the root cause of unobjective student assessment lies in the absence of a diagnostic method of goal-setting in schools. The goal of education must be set diagnostically—that is, so precisely and definitively that one can unequivocally conclude the degree of its realization and achievement [1,2,5,6]. A diagnostic formulation of the educational goal is characterized by learning outcomes expressed in students’ actions, which can be precisely recognized, evaluated, and measured [1,5,6,7].